Bolivia siglo XX. (Plano Medio, 2009)
THE CHACO WAR: BOQUERÓN, the longest and bloodiest international war in our history, facing Paraguay between 1932 and 1935. Historical, political and economic origins of the war. The situation of the two poorest nations on the continent in 1932. Boquerón and the heroism of a small Bolivian military contingent. --